Adequacy of hand positioning by medical personnel during chest compression in a simulation study. Issue 1 (1st May 2021) - Koyama, Yasuaki; Matsuyama, Tasuku; Kainoh, Takako; Hoshino, Tetsuya; Nakao, Junzo; Shimojo, Nobutake; Inoue, Yoshiaki
Abstract : Aim: During chest compressions (CCs), the hand position at the lower half of the sternum is not strictly maintained, unlike depth or rate. This study was conducted to determine whether medical staff could adequately push at a marked location on the lower half of the sternum, identify where the inappropriate hand position was shifted to, and correct the inappropriate hand position. Methods: This simulation‐based, prospective single‐center study enrolled 44 medical personnel. Pressure and hand position during CC were ascertained using a flexible pressure sensor. The participants were divided into four groups by standing position and the hand in contact with the sternum: right–left (R– l ), right–right (R– r ), left–right (L– r ), and left–left (L– l ). We compared the groups and the methods: the manual method (MM), the thenar method, and the hypothenar method (HM). Results: Among participants using the MM, 80% did not push adequately at the marked location on the lower half of the sternum; 60%–90% of the inadequate positions were shifted to the hypothenar side. CCs with the HM facilitated stronger pressure, and the position was minimally shifted to the hypothenar side. Conclusion: Medical staff could not push at an appropriate position during CCs. Resuscitation courses should be designed to educate personnel on the appropriate position for application of maximal pressure while also evaluating the position during CCs. Abstract : Eighty percent of the medical staff could not undertake compression at the adequate position. Nearly 60–90% and 30–50% of inadequate positions were shifted to the hypothenar and forward sides. Chest compression with the hypothenar method was hardly shifted to the hypothenar side.